Island Partitioning of Smart Distribution Systems in Emergencies Considering Voltage and Frequency Stability - Zahra Hosseini Najafabadi; Asghar Akbari Foroud (مجله مدل سازی در مهندسی)
Island partitioning is an attractive solution to restore service in a smart distribution system that becomes islanded unintentionally. Immediately after the disconnection of the main grid due to a fault, the island subsystem experiences intense voltage and frequency deviations. Providing methods for island partitioning without considering frequency and voltage characteristics cannot lead to reliable solutions. So, in this paper, a two-stage and multi-objective solution is presented to restore the services of the island system in emergencies, considering the frequency and voltage stability. In the first stage, according to the available time to decide on the control measures, the partitioning scheme with the aim of the highest restored load and voltage stability margin is presented with the honey badger algorithm. In the algorihm, voltage stability index, load priority and controllability, frequency response and voltage stability margin are included in load shedding and in finding the borders of the partitions, respectively. In the second stage, optimal power flow is done to set the partitions and satisfy the system operational constraints. Not only does the proposed method create partitions with the allowable bus voltage and frequency, but it also privides the lowest losses, the largest restored load, and the highest restored load compared to other methods. Moreover, the proposed method is more comprehensive due to multi-objective and considering voltage stability, frequency stability, simultaneous faults, controllable and uncontrollable distributed generations, reserve, position of switches, available time to decision making, time delay between control measures, and handling islands with positive and negative power imbalance.